Enhanced photocatalytic performance of NiS/ZnO nanocomposite for the remediation of PNP and RhB dye - Pandey S.K.; Mishra P.K.; Tiwary D. (My University, 2025)
A spherical shaped ZnO nanoparticle was combined with a flower like NiS nanoparticle via simple hydrothermal method. The physicochemical properties of the synthesized nanocomposites were observed by using various characterization techniques (HR-XRD, HR-TEM, FE-SEM, EDS, XPS etc.). The photocatalytic performances of the synthesized photocatalysts were monitored by the degradation of p-nitrophenol (PNP) and rhodamine B (RhB) dye under UV-light illumination. The photocatalytic experiment reveals that the synthesized nanocomposites exhibit much higher photocatalytic efficiency than pure ZnO and NiS nanoparticles and removes up to 96% and 93% of PNP & RhB dye respectively via pseudo 1st order kinetics. The observed improvement in the photocatalytic performance of the nanocomposites after the introduction of NiS is mainly due to the separation of useful e-/h+ with strong redox potential at the interface of NiS/ZnO. Moreover, during the photocatalytic experiment we got highest turnover frequency (TOF) for our most efficient nanocomposite (AB-2). The XRD pattern of the used photocatalyst confirms the stability of the nanocomposites. However, the optical band positions and trapping experiment demonstrate that the photocatalytic mechanism proceeds through S-scheme (step scheme). This work gives newer idea to rationalize NiS based hybrid photocatalyts for the removal of pollutants from the environment. © 2022 Elsevier Ltd